San Luis Obispo Buddhist Church Financial Report for 1960 - San Luis Obispo Buddhist Church::::::author::: (1960)
The 1960 financial report for the San Luis Obispo Buddhist Church, which includes income, expenditures, and beginning and ending year balances. It also includes the contributors and their contributions to the fund to acquire an organ for the Church.